An Empirical Research on Factors Affecting Employee Absenteeism in an Airline Industry: A Relook on Job Stress, Work-Life Balance and Job Satisfaction as Predictors - Geydar, Djafarov; Arumugam, Thilageswary; Kuppusamy, Mudiarasan; Singh, Juginder (International Journal of Psychosocial Rehabilitation, 2020)
In today’s world, employee absenteeism became a huge burden for many organizations as it decreases efficiency and effectiveness of the company. Thus, this research was aimed to determine what are the factors influencing employee absenteeism in an airline industry. In this study, employee absenteeism was addressed as a dependent variable. Then, job stress, work-life balance, and job satisfaction were determined as factors contributing to employee absenteeism. There were conducted various analyses like Pearson’s Correlation and Standard Multiple Regression to figure out the relationship between variables. So, as analyses showed, job stress and work-life balance significantly influence employee absenteeism, whereas job satisfaction has insignificant influence and very limited impact on it. This study was mainly developed to help the one of the airline management to reduce absenteeism rate among employees. Clearly, high work life balance and low job stress contributes to lower rate of absenteeism.The implication of the study is sustainable employee competency and productivity achieved by eliminating one important factor such as absenteeism at workplace.